A Model of Minor Histocompatibility Antigens in Allogeneic Hematopoietic Cell Transplantation - Martin, Paul J.; Levine, David M.; Storer, Barry E.; Zheng, Xiuwen; Jain, Deepti; Heavner, Ben; Norris, Brandon M.; Geraghty, Daniel E.; Spellman, Stephen R.; Sather, Cassie L.; Wu, Feinan; Hansen, John A. (Frontiers in Immunology, 2021)
Minor histocompatibility antigens (mHAg) comprised of peptides presented by HLA molecules can cause immune responses involved in graft-versus-host disease (GVHD) and graft-versus-leukemia effects after allogeneic hematopoietic cell transplantation (HCT). The current study was designed to identify individual graft-versus-host genomic mismatches associated with altered risks of acute or chronic GVHD or relapse after HCT between HLA-genotypically identical siblings. Our results demonstrate that in allogeneic HCT between a pair of HLA-identical siblings, a mHAg manifests as a set of peptides originating from annotated proteins and non-annotated open reading frames, which i) are encoded by a group of highly associated recipient genomic mismatches, ii) bind to HLA allotypes in the recipient, and iii) evoke a donor immune response. Attribution of the immune response and consequent clinical outcomes to individual peptide components within this set will likely differ from patient to patient according to their HLA types.